2020
DOI: 10.3390/ijerph17249537
|View full text |Cite
|
Sign up to set email alerts
|

How Does Sexual Harassment Influence the Female Employee’s Negative Response in a Deluxe Hotel?

Abstract: Today, organizations face risky legal and financial consequences stemming from a single sexual harassment event. The purpose of this study was to verify that the sexual harassment, as perceived by female employees, significantly affects their levels of psychological distress and workplace deviant behavior to investigate the moderating role of organizational silence and psychological detachment in the causal relationship. First, this study found that perceived sexual harassment has a negative impact on the fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Previous studies have shown that occupational stigma consciousness can cause more negative work-related outcomes (Van Laar et al, 2019;Clough et al, 2020). Studies on workplace deviant behavior have confirmed that organizational factors could be antecedents or predictors of workplace deviant behavior (Jung and Yoon, 2020). Scholars have called for more investigation of deviant behavior to identify the process of behavior decision-making from the perspective of personal resources (Park et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that occupational stigma consciousness can cause more negative work-related outcomes (Van Laar et al, 2019;Clough et al, 2020). Studies on workplace deviant behavior have confirmed that organizational factors could be antecedents or predictors of workplace deviant behavior (Jung and Yoon, 2020). Scholars have called for more investigation of deviant behavior to identify the process of behavior decision-making from the perspective of personal resources (Park et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, understanding these behaviors and related antecedents has become an important research field (Yildiz et al, 2015). A literature review shows that studies have focused on demographic characteristics (O'Neill et al, 2011;Pletzer et al, 2019), organizational conditions (Dora and Azim, 2019;Kalemci et al, 2019) and workrelated factors (Jung and Yoon, 2020) as antecedents or predictors of workplace deviant behavior. However, few studies have explored uncontrollable cognitive sources within the organization, such as occupational stigma consciousness (O'Neill et al, 2011;Park et al, 2019).…”
Section: Platform Riders' Workplace Deviant Behavior 233mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, an association between sexual harassment in the workplace and suicide and suicide attempts has been found [24]. Moreover, other research carried out in different workplace settings has shown that women who suffer sexual harassment develop psychological distress, which refers to a psychological condition that is characterized by negative thoughts and feelings related to anxiety, fear or depression [25] and need later psychotherapeutic or pharmacologic treatment [23]. In addition, consequences for job-related aspects such as stress, burnout [20] and job withdrawal [22] are associated with sexual harassment.…”
Section: Introductionmentioning
confidence: 99%